The Impact of Gender Dimension on Warfare - Marsili, M. (5th Erasmus Gender Seminar and Military Gender Studies Multiplier Event (Erasmus GS23), 2023)
This work addresses gender dimension and other diversity aspects in warfare, including gender bias in data collection, to go beyond mainstream approaches in policymaking and to infuse gender awareness into conceptual models in international security affairs, according to the elements of a gender-responsive approach to arms control identified by the UN Institute for Disarmament Research (UNIDIR). Gender perspective, based on the resource pack developed by the International Gender Champions (ICG) Disarmament Impact Group helps to shed light on the direct and reverberating impacts of warfare on women, men, girls and boys, such as the likelihood of being targeted by and the long-lasting biological and physiological impacts. focusing on analyzing sex and gender specific effects of emerging and disruptive technologies (EDTs). The 2020 European Commission experts’ report Gendered innovations 2. How inclusive analysis contributes to research and innovation: policy review warns that human bias is amplified by technology, inter alia in the applications of machine learning, artificial intelligence, robotics, facial recognition. Data sources on which this review relies include: UNIDIR, International Federation of Red Cross and Red Crescent Societies (IFRC), Control Arms, Small Arms Survey, MOSAIC Module, Reaching Critical Will, European Institute for Gender Equality. The study aims to enhance the ability of the international community to redress gender inequality in warfare and to mitigate gender impact in armed conflict.